Association of breast cancer risk with polymorphisms in genes involved in the metabolism of xenobiotics and interaction with tobacco smoking: A gene‐set analysis. Issue 8 (14th December 2018) - Berrandou, Takiy; Mulot, Claire; Cordina‐Duverger, Emilie; Arveux, Patrick; Laurent‐Puig, Pierre; Truong, Thérèse; Guénel, Pascal
Abstract : Single nucleotide polymorphisms (SNPs) in genes involved in xenobiotics metabolism (XM) are suspected to play a role in breast cancer risk. However, previous findings based on a SNP by SNP approach need to be replicated taking into account the combined effects of multiple SNPs. We used a gene‐set analysis method to study the association between breast cancer risk and genetic variation in XM genes (seen as a set of SNPs) and in the XM pathway (seen as a set of genes). We also studied the interaction between variants in XM genes and tobacco smoking. The analysis was conducted in a case–control study of 1, 125 cases and 1, 172 controls. Using a dedicated chip, genotyping data of 585 SNPs in 68 XM genes were available. Genetic variation in the whole XM pathway was significantly associated with premenopausal breast cancer risk ( p = 0.008). This association was mainly driven by genetic variation in NAT2, CYP2C18, CYP2C19, AKR1C2 and ALDH1A3 . The association between the XM gene pathway and breast cancer was observed among current and previous smokers, but not among never smokers ( p = 0.013 for interaction between XM genes and tobacco smoking status). The association with breast cancer risk indicates that XM genes variants may play a role in breast carcinogenesis through their detoxification function of environmental pollutants, such as those contained in tobacco smoke. Abstract : What's new? While environmental chemicals are risk factors for breast cancer, little is known about whether their role in cancer etiology is influenced by variations in genes involved in carcinogen breakdown via xenobiotic metabolism (XM). To investigate this question, the authors of the present study analyzed interactions between XM genes and tobacco smoking among breast cancer patients. Among ever‐smokers, single nucleotide polymorphisms in XM genes were associated with premenopausal breast cancer. The association was absent among never smokers. The authors conclude that XM gene variants likely modulate breast cancer risk associated with exposure to tobacco smoke, which contains thousands of toxic chemicals.